Symbols and Interpersonal Meanings of Popular Love Songs (Journal of Innovative Research, 2025)
This study ventured to analyze the select popular love songs. It employed a qualitative research approach using linguistic and rhetorical criticism. Systemic Functional Linguistics of M. A. K. Halliday, Fantasy Theme Criticism, and Semiotics were the analyses applied in order to discover the interpersonal meanings and symbols that select popular love songs carry in their lyrics. The researcher analyzed ten (10) songs. The following statistical tools were employed to analyze the data gathered: frequency count and percentage distribution. The research discovered that the mood and modality present in the lyrics of the songs were the two components to consider in determining the interpersonal meanings. On the other hand, the swirling of three themes: setting, character, and actions, form a successful rhetorical vision. The fantasy themes present in love songs, taken together, reveal the worldview created in different contexts of relationships built by love. Salient themes in the songs are breakups, deeply falling in love, regrets, and self-love which codes that encompass the themes are the characters, settings, and actions. The popular love songs invite the rhetorical community to perceive love in many mirrors. Symbols are also present in the lyrics of the songs. The symbols generated from the lines of the songs have a message intended for the addressees. The symbols represent a particular idea, theme, or meaning that the persona would want to communicate to the addressees. Based from the results of the analyses, various strategies in teaching language and literature were made and it is concluded that songs are best to integrate in the teaching of language and literature. It is also recommended that researchers conduct more studies that aim to explore more effective strategies in teaching language and literature utilizing different kinds of poetry.